Development and internal validation of a clinical prediction model for 90-day mortality after lung resection: the RESECT-90 score. (29th July 2021) - Taylor, Marcus; Martin, Glen P; Abah, Udo; Sperrin, Matthew; Smith, Matthew; Bhullar, Dilraj; Shackcloth, Michael; Woolley, Steve; West, Doug; Shah, Rajesh; Grant, Stuart W; ,
Abstract:  : OBJECTIVES: The ability to accurately estimate the risk of peri-operative mortality after lung resection is important. There are concerns about the performance and validity of existing models developed for this purpose, especially when predicting mortality within 90 days of surgery. The aim of this study was therefore to develop a clinical prediction model for mortality within 90 days of undergoing lung resection. METHODS: A retrospective database of patients undergoing lung resection in two UK centres between 2012 and 2018 was used to develop a multivariable logistic risk prediction model, with bootstrap sampling used for internal validation. Apparent and adjusted measures of discrimination (area under receiving operator characteristic curve) and calibration (calibration-in-the-large and calibration slope) were assessed as measures of model performance. RESULTS: Data were available for 6600 lung resections for model development. Predictors included in the final model were age, sex, performance status, percentage predicted diffusion capacity of the lung for carbon monoxide, anaemia, serum creatinine, pre-operative arrhythmia, right-sided resection, number of resected bronchopulmonary segments, open approach and malignant diagnosis. Good model performance was demonstrated, with adjusted area under receiving operator characteristic curve, calibration-in-the-large and calibration slope values (95% confidence intervals) of 0.741 (0.700, 0.782), 0.006 (−0.143, 0.156) and 0.870 (0.679, 1.060), respectively. CONCLUSIONS: The RESECT-90 model demonstrates good statistical performance for the prediction of 90-day mortality after lung resection. A project to facilitate large-scale external validation of the model to ensure that the model retains accuracy and is transferable to other centres in different geographical locations is currently underway. Abstract : Many risk models designed to predict short-term mortality after lung resection have been developed over the last 30 years and are considered an important part of the pre-operative risk assessment process.